2015
DOI: 10.1093/infdis/jiv031
|View full text |Cite
|
Sign up to set email alerts
|

A Thermonuclease ofNeisseria gonorrhoeaeEnhances Bacterial Escape From Killing by Neutrophil Extracellular Traps

Abstract: Acute gonorrhea is characterized by neutrophilic inflammation that is insufficient to clear Neisseria gonorrhoeae. Activated neutrophils release extracellular traps (NETs), which are composed of chromatin and decorated with antimicrobial proteins. The N. gonorrhoeae NG0969 open reading frame contains a gene (nuc) that encodes a putatively secreted thermonuclease (Nuc) that contributes to biofilm remodeling. Here, we report that Nuc degrades NETs to help N. gonorrhoeae resist killing by neutrophils. Primary hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 34 publications
0
62
0
Order By: Relevance
“…The failure to detect Nuc or its DNA-degrading activity in the supernatant led to the suggestion that Nuc may be localized in the periplasm (8). In a recent study, Nuc was found to have extracellular activity, but it remained unclear whether extracellular Nuc arose through secretion or through lysis (9). The fact that Nuc contains an N-terminal signal peptide supports the idea that Nuc resides within the periplasm at least transiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure to detect Nuc or its DNA-degrading activity in the supernatant led to the suggestion that Nuc may be localized in the periplasm (8). In a recent study, Nuc was found to have extracellular activity, but it remained unclear whether extracellular Nuc arose through secretion or through lysis (9). The fact that Nuc contains an N-terminal signal peptide supports the idea that Nuc resides within the periplasm at least transiently.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of gonococcal chromosomal DNA limits Nuc's activity. Moreover, Nuc can degrade neutrophil extracellular traps (9). While Nuc carries a signal peptide for secretion, active secretion into the supernatant has not been observed, and therefore, a periplasmic location was proposed (8).…”
mentioning
confidence: 99%
“…Seper and colleagues (38) found that a Vibrio cholerae strain deficient for two extracellular nucleases, deoxyribonuclease and xds, was less invasive than wild-type V. cholerae in immunocompetent mice, although no difference between strains was seen in neutropenic mice, and quantitative RT-PCR revealed that the presence of either NETs or DNA was able to up-regulate the expression of deoxyribonuclease and xds (38). Neisseria gonorrheae has also been shown to encode the heat-stable nuclease, nuc, thought to be important for remodeling N. gonorrheae biofilms (39). NETs were shown to be rapidly induced by N. gonorrheae, but thereafter NET integrity decreased over time in nuccontaining strains compared with a Dnuc mutant, as measured by Sytox Green immunofluorescence.…”
Section: Other Pathogens: Net Degradationmentioning
confidence: 99%
“…periodontopathogenic bacteria can produce extracellular nucleases (367,375). Recently, it was determined that Neisseria gonorrhoeae encodes for a heat-stable thermonuclease (Nuc), which provides the bacterium an effective virulence factor against NETs, as it is capable of DNA degradation (396). After NETs were produced, the presence of thermonuclease aided the bacterium in degrading the DNA and enhancing their survival capabilities (396).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was determined that Neisseria gonorrhoeae encodes for a heat-stable thermonuclease (Nuc), which provides the bacterium an effective virulence factor against NETs, as it is capable of DNA degradation (396). After NETs were produced, the presence of thermonuclease aided the bacterium in degrading the DNA and enhancing their survival capabilities (396). No significant reduction in NET formation when NETs stimulated with PMA are then exposed to F. alocis broth or growth supernatant (data not shown) which suggests that although F. alocis possesses a thermonuclease, it may be present at a low concentration, therefore deeming it ineffective in degradation of NETs.…”
Section: Discussionmentioning
confidence: 99%